Development of collaborative based inquiry learning tools using local wisdom context to improve students metacognitive - Sri Supiyati; Muhammad Halqi; Edy Waluyo; Ahmad Rasidi (Jurnal Elemen, 2023)
Geometry is one of the essential materials for students. However, geometry material, especially the concept of geometry, still needs to be made more accessible for students. Models and media are needed, and the proper context in learning mathematics in geometric material. Therefore, this research aims to develop valid, practical, and effective learning using the Collaborative Based Inquiry learning model based on local wisdom to improve students' metacognitive abilities. This study is Research and Development (R & D). There were five stages in this study: to analyze the developed product, develop the initial product, expert validation and revision, small-scale field trials and product revisions, and large-scale field trials and final products. Based on the results of the study obtained, several research conclusions, including that the learning device was valid. From the limited test, the results of the five ability test questions were obtained metacognitive is also valid and reliable. Developed learning plans as well practicals from the side of teachers and students. Moreover, the average value of students' metacognitive abilities in the experimental class is classified as effective to increase students' metacognitive abilities. That way, learning mathematics design with Collaborative Based Inquiry based on local wisdom can improve students' metacognitive abilities.